Analisis Pendapatan Daerah di Era Otonomi Pada Pemerintah Kabupaten Induk dan Kabupaten Pemekaran - Halkadri Fitra (Wahana Riset Akuntansi, 2014)
The purpose of this study was to determine the level of independence, ability, effectiveness and dependence of local financial  dependence on the original local government and new  local government with a case study on the Pasaman and Pasaman Barat for the period 2008-2013. This research is descriptive research and the use of secondary data. Based on the analysis found that the ratio of the level of local financial independence Pasaman was 4.88% and was 5.38%  Pasaman Barat with assessment criteria both in very poor condition. To the level of local financial capacity Pasaman obtain the results of  Pasaman 101.40% and 100.64%  for Pasaman Barat t with the result of the very good category, then the level of effectiveness of local revenues with local governments Pasaman 102.83% and the result is 93.87% for Pasaman Barat with a very effective criteria, than  regional financial dependence Pasaman with value 95.10% and 93.35%  for Pasaman Barat with a very high dependence criteria.. Keywords: independence, ability, effectiveness and dependence.